2021
DOI: 10.1200/jco.21.00662
|View full text |Cite
|
Sign up to set email alerts
|

Amivantamab in EGFR Exon 20 Insertion–Mutated Non–Small-Cell Lung Cancer Progressing on Platinum Chemotherapy: Initial Results From the CHRYSALIS Phase I Study

Abstract: PURPOSE Non–small-cell lung cancer (NSCLC) with epidermal growth factor receptor ( EGFR) exon 20 insertion (Exon20ins) mutations exhibits inherent resistance to approved tyrosine kinase inhibitors. Amivantamab, an EGFR-MET bispecific antibody with immune cell–directing activity, binds to each receptor's extracellular domain, bypassing resistance at the tyrosine kinase inhibitor binding site. METHODS CHRYSALIS is a phase I, open-label, dose-escalation, and dose-expansion study, which included a population with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
292
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 400 publications
(368 citation statements)
references
References 35 publications
6
292
2
Order By: Relevance
“…These findings are clinically meaningful considering the 136 population of interest is relapsed metastatic or unresectable NSCLC with a 5-year survival rate of less than 10%. 25 For full approval, the FDA will require results of a Phase III trial. The phase III PAPILLON trial (NCT04538664) is currently investigating amivantamab in combination with carboplatin-pemetrexed chemotherapy compared to chemotherapy alone in the first line treatment setting of metastatic NSCLC with exon 20 insertion mutations.…”
Section: Discussion/future Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are clinically meaningful considering the 136 population of interest is relapsed metastatic or unresectable NSCLC with a 5-year survival rate of less than 10%. 25 For full approval, the FDA will require results of a Phase III trial. The phase III PAPILLON trial (NCT04538664) is currently investigating amivantamab in combination with carboplatin-pemetrexed chemotherapy compared to chemotherapy alone in the first line treatment setting of metastatic NSCLC with exon 20 insertion mutations.…”
Section: Discussion/future Directionsmentioning
confidence: 99%
“…In vitro studies showed saturation of circulating free EGFR began after a single dose of 350 mg and saturation of MET at a single dose of 140 mg. Complete and durable saturation of both EGFR and MET was reliably achieved at doses ≥700 mg. 25 …”
Section: Pharmacodynamic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, amivantamab, an EGFR-MET bispecific antibody, was recently approved to treat EGFR ex20ins NSCLC patients ( 30 ). This approval was based on the results of a phase 1 trial CHRYSALIS (NCT02609776) in which amivantamab achieved an ORR of 40% (95% CI: 29%, 51%) and a median response duration of 11.1 months (95% CI: 6.9, not evaluable) ( 31 ).…”
Section: Discussionmentioning
confidence: 99%